FACTORS ASSOCIATED WITH THE INCIDENCE OF LOW BACK PAIN BASED ON THE NUMERIC PAIN RATING SCALE IN DAILY WORKERS AT THE BBPPT KOMINFO DEPOK PROJECT - Nur Romdhona; Salsabila Nuraini; Fini Fajrini; Noor Latifah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Low back pain (LBP) is pain that is felt in the lower back area and originates in the spine, muscles, nerves, or other structures around the area. The prevalence rate of LBP in Indonesia in 2016 was 59.25%. This study aims to determine the factors associated with the incidence of low back pain in daily workers at the BBPPT Kominfo Depok project.Quantitative research with a cross-sectional study design. The population is daily field workers with a total of 70 people and the sampling technique is total sampling. Data collection was carried out in January 2023. Data analysis used the chi-square test α = 0.05. From the study results, the p-value of each variable was obtained, namely: Age (p-value 0.071 meaning that there is no significant relationship between age and the incidence of LBP), Body Mass Index (BMI) (p-value 1.000 meaning there is no significant relationship between BMI with the incidence of LBP), Smoking Habit (p-value 0.044 means that there is a significant relationship between smoking habits and the incidence of LBP), Working Mass (p-value 0.042 means that there is a significant relationship between working mass and the incidence of LBP), Working Time (p-value 0.017 means that there is a significant relationship between working time and the incidence of LBP) and Lifting Weight (p-value 0.013 means that there is a significant relationship between the lifting weight and the incidence of  LBP). Smoking habits, years of service, length of work, and weight of lifting have a relationship with the incidence of LBP. Reducing the length of work for daily workers so that daily workers get sufficient rest time, and providing an adequate number of assistive devices so that workers do not lift objects or materials manually.